A survey study on some neurological symptoms and sensations experienced by long term users of mobile phones - Balikci, K; Ozcan, IC; Turgut-Balik, D; Balik, HH (Elsevier France-Editions Scientifiques Medicales Elsevier, 2005)
A survey study was conducted to investigate the possible effects of mobile phone on headache, dizziness, extreme irritation, shaking in the hands, speaking falteringly, forgetfulness, neuro-psychological discomfort, increase in the carelessness, decrease of the reflex and clicking sound in the ears. There is no effect on dizziness, shaking in hands, speaking falteringly and neuro-psychological discomfort, but some statistical evidences are found that mobile phone may cause headache, extreme irritation, increase in the carelessness, forgetfulness, decrease of the reflex and clicking sound in the ears. (C) 2004 Elsevier SAS. All rights reserved.
Keywords: neurological symptoms; mobile phones; long term usage; biological effects; microwave